Management of complete dislocation of tarsal scaphoid without fracture - Ansari, M. A. Q.; Mayi, Shivanand; Shah, Sachin A. (International Journal of Research in Orthopaedics, 2017)
Background: Injuries to the mid tarsal joints usually occur in the form of various combinations such as fracture, fracture subluxation, and fracture dislocation. Dislocations of navicular without fracture are rare injuries, minimal literatures exist, which describe the probable mechanism of injury and optimal treatment. Methods: Four patients with complete dislocation of navicular without fracture presented to us following a history of trauma. The diagnosis was confirmed by radiology and further details were studied by CT scans. One injury was open and the rest were closed. One had associated fracture of talus and two had metatarsal fracture and one was purely isolated navicular dislocation without any associated injury. All were initially stabilized in a below knee plaster of paris slab and foot end elevated. All were successfully treated surgically under spinal anesthesia with open reduction and internal fixation with Kirschner wires through a dorsomedial approach. Postoperative immobilization was continued for twelve weeks then gradual mobilization begun followed by physiotherapy. Results: All patients had good clinical results with two patients resuming their work within twelve weeks and the one with open wound took twenty weeks for resuming his original work. One with associated talar fracture later had to undergo subtalar arthrodesis for pain in the foot while weight bearing after one year of surgery for navicular dislocation. Conclusions: Open reduction and internal fixation with Kirschner wire is an effective way of managing patients with complete dislocation of tarsal navicular for early resuming of the functions and return to work.